Penerapan TPACK Terhadap Peningkatan Prestasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam Kelas XI F1 di SMA Negeri 2 Sipora - Muhamad Haiqal (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education using the Technological Pedagogical Content Knowledge (TPACK) approach among 11th-grade students at SMA Negeri 2 Sipora. This classroom action research consisted of two cycles, each encompassing planning, implementation, observation, and reflection stages. The results indicated that only 23% of students achieved the Learning Objective Mastery Criteria (KKTP) during the pre-cycle. After applying the TPACK approach, learning mastery increased to 93.3% in the second cycle. This improvement was driven by the use of technology-based learning media, varied teaching methods such as group discussions, and active student engagement in the learning process. The study demonstrates that the TPACK approach effectively enhances student learning outcomes, especially in technology-integrated education relevant to students' needs.